PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Simarmata, Ester Julinda; Sitanggang, Robertus; Sinaga, Reflina; Lumbanraja, Bogor; Ambarwati, Nova Florentina; Tanjung, Darinda Sofia (Universitas Negeri Medan, 2024)
This research aims to determine the effect of the inquiry learning model on student learning outcomes in class IV Mathematics at SD Negeri 22 Sigaol Marbun for the 2023/2024 academic year. The research method used is an experimental method with a quantitative research type. To obtain the data required a test instrument of 25 questions. The total research sample was 31 students based on purposive sampling technique. To determine students' initial abilities, the research conducted a Pre Test with an average score of 56.77 which was included in the poor category. The results of the Post Test have improved from the Pre Test results given previously with the students' average score reaching 73.29 in the good category. It can be said that the level of success in student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation, which obtained r_count ≥r_tabel with results of 0.716 ≥ 0.355. Next, hypothesis testing compares the t_count ≥t_table value. The obtained value of t_count = 5.523 while t_table = 1.696. Because t_count ≥t_table (5.523 ≥ 1.696) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Inquiry learning model (X) on student learning outcomes (Y).